STUDI KOMPARATIF PENGADAAN TANAH DAN GANTI KERUGIAN DALAM KONSTRUKSI HUKUM DI INDONESIA DAN INDIA - Catherine Kezia Rahmayanti, (2022)
The revocation of rights in Indonesia and the Eminent Domain in India in the effort to acquire land for the public interest is a process that often leads to conflict. The stages of land acquisition and compensation in each country are interesting to discuss. According to Indonesian law, land acquisition is regulated in Government Regulation Number 19 of 2021 and goes through the stages of planning, preparing, implementing, and submitting the results of land acquisition. The implementation of compensation in Indonesia begins with the Land Appraiser calculating the value of the loss of the Land Procurement Object, including: land; Above Grounds and Dungeons; building; plant; objects related to land; and other assessed losses. Then compensation is given to the Entitled Party. According to Indian law, land acquisition for public interest is regulated in The Right to Fair Compensation and Transparency in Land Acquisition, Rehabilitation and Resettlement Act, 2013 and goes through the stages of notification of advance, land survey, filing of objections, rehabilitation & resettlement schemes, declaration of land acquisition, notification of the implementation of land acquisition, and submission of compensation. The implementation of compensation in India is carried out by the Collector and the amount of compensation determined by the Collector must meet the solatium which sis equivalent to one hundred percent of the total compensation and an amount calculated at 12% per annum at the market value of that year. After all calculations are complete, the Collector will report to the project chief executive and compensation will be given to the Land Owners.